Features of Business Process Management in the Context of Digital Transformation - Reshetnyak Olena I.; Zhykhor Olena B.; Yurchenko Oleksii K.; Zhykhor Bohdan I. (Bìznes Inform, 2025)
The article examines the peculiarities of business process management in the context of digital transformation of modern entrepreneurship. The aim of the study is to characterize the features of business process management within the framework of digitalization, including identifying directions for improvement and key requirements for implementing transformational changes. It has been determined that digitalization is one of the key factors in increasing the efficiency of companies’ operations and achieving their competitive advantages in the market. Digital transformation is viewed as a comprehensive process that integrates innovative technologies with the strategic use of enterprise resources, creates additional opportunities, and revises the value proposition for all stakeholders. It is noted that transformation encompasses profound changes in the organization of business that require new approaches to thinking, labor organization, and interaction with consumers. The importance of business process reengineering, which is a necessary component of digital transformation, is emphasized. Optimization of processes allows for increased efficiency, reduced costs, improved quality of products and services, and ensures the prompt processing of data, which in turn facilitates faster adaptation to changes in the market and the technological environment. Attention is called to the consideration that digital transformation requires enterprises to be ready for constant changes, the implementation of new business models, and processes. The main advantages of applying digital technologies in business management are highlighted as follows: increased labor productivity, decreased operating costs, continuity of production and social processes, and quick responses to changes in the environment. It is determined that the organization of business processes in modern conditions increasingly intersects with the challenges of digitalization, opening new perspectives for research into the impact of technology on organizational activities and strategic management. Along with this, the implementation of digital technologies is accompanied by challenges and risks, which makes it important for enterprises to carefully assess the opportunities for digital transformation, prepare personnel for changes, and create flexible adaptation systems. An important condition for successful digital transformation is the implementation of an ambidextrous approach to business process management, which involves simultaneously improving existing processes (operational approach) and seeking new opportunities through radical innovations (research approach). Effective management of business processes using digital technologies provides stable growth for companies and increases their innovativeness, adaptability, and resilience to global challenges.